2020
DOI: 10.1186/s13018-020-01604-x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and identification of synovial tissue-derived exosomes by different separation techniques

Abstract: Objective: The aim of this study is to compare the efficiency of different separation techniques for extracting synovial tissue-derived exosomes. Methods: The synovial tissue discarded during knee arthroscopy or total knee arthroplasty surgery was collected from the Third Affiliated Hospital of Beijing University of Chinese Medicine. Ultracentrifugation (UC), filtration combined with size exclusion chromatography (SECF), and 8% polyethylene glycol (PEG) were used to extract synovial tissue-derived exosomes. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 30 publications
1
34
1
Order By: Relevance
“…Since a single exosome isolation technique cannot reach optimal yield and purity, coupling SEC with other isolation methods including dUC, UF, or PEG-based retrieval can precipitate intact, highly purified exosomes in a reproducible manner. However, the limitations of these approaches as detailed above will then accompany the chimeric protocol [ 32 , 37 , 44 , 49 , 90 , 101 , 102 , 103 ].…”
Section: Ideal Methods For Exosome Isolation: Secmentioning
confidence: 99%
“…Since a single exosome isolation technique cannot reach optimal yield and purity, coupling SEC with other isolation methods including dUC, UF, or PEG-based retrieval can precipitate intact, highly purified exosomes in a reproducible manner. However, the limitations of these approaches as detailed above will then accompany the chimeric protocol [ 32 , 37 , 44 , 49 , 90 , 101 , 102 , 103 ].…”
Section: Ideal Methods For Exosome Isolation: Secmentioning
confidence: 99%
“…A loading buffer was then added, mixed well, exposed to a metal bath at 95°C for 5 min, and stored at −80°C after dispensing. Western blot (WB) analysis was performed in accordance with a method described previously ( Chen et al., 2019 ; Chen et al., 2020 ). Briefly, equal amounts of protein (40 μg) were separated using sodium-dodecyl polyacrylamide gel electrophoresis, loaded onto the 8%–12% separation gel according to the target molecular weight, and then transferred onto a polyvinylidene fluoride (PVDF) membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al compared the efficiency of three separation techniques (ultracentrifugation, filtration combined with size exclusion chromatography and 8% polyethylene glycol) for extracting synovial tissue-derived exosomes (Syn-Exos). 261 They found that the efficiency of exosome isolation differed among these three isolation methods and recommended ultracentrifugation and filtration combined with size exclusion chromatography for the extraction of Syn-Exos. 261 Therefore, additional measures are needed to optimize and standardize the existing separation methods so that the clinical use of MSC-Exos is safe and convenient.…”
Section: Perspectivementioning
confidence: 99%